Integration of ESG (Environmental, Social, Governance) principles with SDGs (Sustainable Development Goals) #3 Wellness - Sustainable Lifestyle Business Model - YEUNG, Shirley M C (Journal of Ecohumanism, 2025)
Emergence of business usually goes along with new demands of customers, for example, design of SDG#3 wellness related services were on the rise in the past few years. Design thinking, SERVQUAL model and UNSDGs are applied into the design and management of new demands of professional services under technological advancement in a society. In order to understand the factors leading to SDG#3 wellness model in halo salt therapy, twenty-two articles published from 2006 to 2025 were analysed. It is found that sustainable lifestyle in habit with rock salt, natural environment creation, safe complementary therapy, degree of improvement in quality of life are the key elements for sustainable wellness business. An interview has been conducted with an expert on halo salt therapy practitioner to validate the factors on the creation of the natural environment – touchless and non-invasive. This paper is of practical value in terms of understanding the key elements for sustainable wellness business through re-visiting the ways of educating the community on professional services on halo salt therapy, making use of advanced technology, and exploring the ways of measuring the business and social impacts generatetd from wellness business models. This brings insights to industry practitioners, investors, educators and policy makers on the importance of tracing the trend of emerging industry for sustainable development.